2017
DOI: 10.5005/jp-journals-10024-2039
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Orthodontic Treatment by Fixed or Myofunctional Appliances and Periodontitis: A Retrospective Study

Abstract: Introduction Malocclusion plays an important role in the development of periodontitis. Thus, by treating malocclusion, a good gingival health can be achieved. This study was conducted to establish the correlation between orthodontic tooth movement and periodontitis. Materials and methods This is a retrospective study conducted on 220 patients who underwent orthodontic treatment for malocclusion. They were divided into two groups: Group I patients were treated with fixed orthodontics, while group II patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, the effect of orthodontic treatment on gingival atrophy is controversial. Some scholars have found that correct orthodontic treatment can help to improve gingival recession, whereas other scholars believe that orthodontic treatment can cause or aggravate gingival recession [ 14 , 15 ]. These studies have not involved teeth with low occlusal function; thus, the effect of orthodontic treatment on gingival status in patients with low occlusal function is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of orthodontic treatment on gingival atrophy is controversial. Some scholars have found that correct orthodontic treatment can help to improve gingival recession, whereas other scholars believe that orthodontic treatment can cause or aggravate gingival recession [ 14 , 15 ]. These studies have not involved teeth with low occlusal function; thus, the effect of orthodontic treatment on gingival status in patients with low occlusal function is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patients with a prior history of periodontitis should undergo treatment for the disease before initiating orthodontic tooth movement [10]. It is therefore recommended to conduct a thorough periodontal examination before and during orthodontic treatment to monitor the condition of periodontal tissues [5,12].…”
Section: Orthodontic Treatment and Periodontal Healthmentioning
confidence: 99%
“…An Orthodontic treatment is essential for resolving malocclusion and improving oral hygiene by removing plaque, improving occlusal stability, and harmonizing with perioral muscles to eliminate dysfunction [4,5]. Moreover, it has been reported that the elimination of malocclusion increases self-esteem and social acceptance, which has a significant impact on the quality of life [6].…”
Section: Introductionmentioning
confidence: 99%
“…Gingival recession consists in apical displacement of the gingival margin leading to esthetic problems, dentin hypersensitivity and possible development of erosion and caries lesions [ 9 ]. Many factors are associated with gingival recessions and previous studies related to gingival recession and orthodontic movement [ 10 , 11 ]. A possible explanation for gingival recession after orthodontic treatment is bone dehiscence development related to tooth movement against the labial/buccal bone plate.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for gingival recession after orthodontic treatment is bone dehiscence development related to tooth movement against the labial/buccal bone plate. In this context, labial movement of mandibular incisors promoted by fixed functional appliances would be a predisposing factor for gingival recessions in the long term [ 10 ]. According to Garib et al [ 12 ], incisor buccolingual movements are considered the most critical orthodontic movement predisposing to bone dehiscence.…”
Section: Introductionmentioning
confidence: 99%